Methotrexate-resistant Chinese hamster ovary cells have amplified a 135-kilobase-pair region that includes the dihydrofolate reductase gene. - Milbrandt, J D (1981)
For the eventual purpose of isolating and studying a single animal cell replicon, we have developed a methotrexate-resistant Chinese hamster ovary cell line that has amplified an early-replicating DNA sequence approximately 500 times; this sequence includes the gene coding for dihydrofolate reductase (DHFR; tetrahydrofolate dehydrogenase; 5,6,7,8-tetrahydrofolate:NADP+ oxidoreductase, EC 1.5.1.3). DHFR composes 30% of the cytoplasmic protein in this cell line, and DHFR mRNA represents 25% of the message translatable in vitro. After digestion of genomic DNA from resistant cells with restriction enzymes, a unique set of highly repetitive restriction fragments can be visualized on agarose gels by ethidium bromide staining. These bands are not present in digests of parental DNA. We estimate the total length of the unit repeated sequence to be 135 +/- 15 kilobase pairs. Regardless of the restriction enzyme utilized, a subset of these repetitive fragments hybridizes to radioactive DHFR cDNA. The homogeneously staining regions on mitotic chromosomes in which these amplified sequences are located are shown to be early-replicating, as are the highly repeated restriction fragments themselves. These data suggest that an early replicon can be isolated from this region, and that this entire, normally unique, genomic segment can be cloned and mapped with respect to origins of DNA synthesis and promoters for transcription, as well as other genetic features of interest.